Implementasi Metode Pra-Experimental Designs Untuk Meningkatkan Sikap Ilmiah Dan Literasi Sains Pada Praktikum Fisika Materi GLB Siswa Ma Al-Iman Bulus Purworejo - Endang Yulyanti; Umi Pratiwi (Lontar Physics Today, 2022)
Education is very important in one's life. A student must have a good scientific attitude so that the learning process runs smoothly. In the learning process doing physics practicum so that the material is better understood. This practicum was carried out using the Pre-Experimental Designs method. This method is used to improve the scientific attitude and scientific literacy of students who are still low through physics practicum. This practicum was carried out on offline uniform motion material (GLB) in class X MIPA 1 MA Al-Iman Bulus Purworejo with 35 students and divided into 4 groups. The results of the research in class X MIPA 1 MA Al-Iman Bulus Purworejo showed that the scientific attitude of the students was good, namely in terms of curiosity, discipline, responsibility and cooperation. The results showed that there was an increase in the results of the pretest and posttest carried out before and after the practicum. The average pretest score obtained is 7.1 8.0 then the posttest score is 8.1 9.0. The data proves that practicum activities using the Pre-Experimental Designs method can improve the scientific attitude and scientific literacy of class X MIPA 1 MA Al-Iman Bulus Purworejo students.Keywords : Scientific Attitude, Pre-Experimental Designs, Scientific Literacy